Caracterização de amidos de rizomas do Hedychium coronarium (lírio-do-brejo) in natura e modificados por fosfatação - Oliveira, Tatielih Pardim de (2012)
The lily of the marsh (Hedychium coronarium) is an invasive plant with high proliferation capacity for rhizomes, and it can be utilized as a new non-conventional source of starch for different uses. Since there is no information available in the literature on the chemical modification of this starch, the present work aimed to study the characteristics of natural and modified starch according to the phosphating reaction time (20, 30 and 40 min) and concentration of sodium tripolyphosphate (3, 5 and 7%). The chemical composition, density, size and shape of starch granules of each sample were determined by light microscopy and scanning electron microscopy, swelling power and solubility index, X-ray diffraction, differential scanning calorimetry, infrared spectroscopy with spectroscopy and nuclear magnetic resonance. The natural starch granules presented an ellipsoid and irregular pentagonal shape with average length and width from 44.7 to 57.1 and from 29.9 to 36.4 μm, respectively. The linear regression model was adjusted to ash and phosphorus levels, and an increase of these levels was verified with increasing concentration of TPS and reaction time. The greatest effect was exerted by the concentration of TPS. When it comes to the dimensions of the phosphate granules, a slight increase was observed. With the methodology used, it was possible to obtain lily of the marsh starches with levels of phosphorus acceptable by the legislation for food with phosphating levels of 3% and 5%. Phosphorus concentrations above 0.4% were obtained in samples with 7% of TPS, which suggests the functional application of those in other technological purposes. The samples of starch phosphate studied presented reduced density, increase in swelling power and solubility rate, and a greater degree of crystallinity. In the analysis of NMR, there were signs at 2.74 ppm, which indicates the presence of inorganic phosphate or starch phosphate monoester, and a signal at 0.16 ppm, indicative of the presence of phosphodiester bond, which is an indication that the phosphorylation reaction was effective and that the starch-phosphate binding occurred with the formation of monoester forms and starch phosphate diester.